The man who killed Hitler and then the Bigfoot [videorecording (DVD)] - Krzykowski, Robert D., 1984-; Berenson, Shaked; Berenson, Shaked; Elliott, Sam, 1944-; Turner, Aidan, 1983-; Fitzgerald, Caitlin (Actor) (RLJE Films, 2019)
Since WWII, Calvin Barr has lived with the secret that he was responsible for the assassination of Adolf Hitler. Now, decades later, the US government has called on him again for a new top-secret mission. Bigfoot has been living deep in the Canadian wilderness and is carrying a deadly plague that is now threatening to spread to the general population. Relying on the same skills that he honed during the war, Calvin must set out to save the free world yet again.